Privacy Protection of VLSI Circuits through High Level Transformation based Obfuscation - Anjum, Farha; lliyas, Mohammad (International Journal of Engineering and Technology, 2018)
This paper focuses on â€œsemiconductor manufacturing obliges greater capital investments, the utilization for contract foundries need developed dramatically, expanding exposure to robbery and unapproved overabundance generation. A significant number of exercises demonstrated that IC piracy has currently turned into a real challenge for the electronics and defense industries. In this manuscript we displays a new approach to configure complicated circuits for digital signal processing (DSP) provisions utilizing high-level transformations, a key-based obfuscating finite-state machine (FSM), and a reconfiguration. The aim is to design DSP circuits, which would harder to reverse engineer. With a few modes for operations for obfuscation where the outputs are expressive from a signal processing point for view, however are functionally inaccurate to preferred perplexity. The design information controls different mode of the circuit process and useful obfuscation will be refined with the utilization of the correct initialization key. Structural obfuscation will be also attained by the recommended procedure through high-level transformations. The effectiveness of suggested procedure will be checked with FIR configuration strong high level obfuscation may be demonstrated and investigated for different key sizesâ€. Â Â